Beckett and the cognitive method - Bernini, Marco (Oxford University Press, 2021)
Does literature merely represent cognitive processes, or can it enhance, parallel, or reassess the scientific study of the mind? 'Beckett and the Cognitive Method' argues that Samuel Beckett's narrative work, rather than just expressing or rendering mental states, inaugurates an exploratory use of narrative as an introspective modeling technology. Through a detailed analysis of Beckett's entire corpus and published volumes of letters, this book argues that Beckett pioneered a new method of writing to construct (in a mode analogous to scientific inquiry) models for the exploration of core laws, processes, and dynamics in the human mind. Marco Bernini integrates frameworks from contemporary narrative theory, cognitive sciences, phenomenology, and philosophy of mind to make a case for Beckett's modeling practice.
10.1093/oso/9780190664350.001.0001
Keywords: Beckett; Samuel; Kognition; Bewusstsein; Bewusstseinszustand; Cognition in literature